Anthocyanins and flavonoids derived from Clitoria ternatea L. flower inhibit bladder cancer growth via suppressing fatty acid synthesis mediated by SREBP1 pathway - Liu Chenkai; Liu Jue; Liu Gao; Song Yusong; Yang Xiuyu; Gao Honglei; Xiang Cheng; Sang Jie; Xu Tianrui; Sang Jun (Acta Biochimica et Biophysica Sinica)
Clitoria ternatea L. flowers are used as traditional herbal medicines and are known for their advanced pharmacological activities. Flavonoids and anthocyanins reportedly contribute to the therapeutic properties of C. ternatea flowers; however, their potential anti-bladder cancer effects and molecular mechanisms remain unknown. In this study, flavonoid- and anthocyanin-rich samples from C. ternatea flowers (DDH) are prepared via macroporous resin-based extraction coupled with an efficient and reliable two-dimensional UPLC-DAD-MS/MS method. In vitro and in vivo studies reveal that DDH can inhibit bladder cancer cell growth and enhance the anti-bladder cancer activity of cisplatin. RNA-seq combined with KEGG analysis reveals that fatty acid synthesis is closely related to the anti-bladder cancer effect of DDH. Furthermore, DDH dose-dependently reduces cellular fatty acid levels in bladder cancer cells, and the addition of fatty acids significantly mitigates DDH-induced cell growth inhibition. Subsequent findings reveal that DDH downregulates sterol regulatory element-binding protein 1 (SREBP1), a key transcriptional regulator of de novo fatty acid synthesis in cancer cells, and its downstream targets (FASN, SCD1, and ACC). Additionally, this study demonstrates that gallic acid not only enhances the stability of DDH but also synergistically potentiates its anti-bladder cancer activity. Our study suggests that targeting the SREBP1 pathway is an effective strategy in bladder cancer therapy, and the ability of DDH to induce cell death by inhibiting the SREBP1 pathway and its good tolerance in mice make it a promising strategy for preventing and treating bladder cancer.